2004
DOI: 10.1161/01.res.0000120861.27064.09
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox A9 Transcriptionally Regulates the EphB4 Receptor to Modulate Endothelial Cell Migration and Tube Formation

Abstract: Abstract-Homeobox genes (Hox) encode for transcription factors, which regulate cell proliferation and migration and play an important role in the development of the cardiovascular system during embryogenesis. In this study, we investigated the role of HoxA9 for endothelial cell migration and angiogenesis in vitro and identified a novel target gene,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 51 publications
(60 reference statements)
5
122
1
1
Order By: Relevance
“…Bruhl et al . reported that HOXA9 bound to the EphB4 promoter and stimulated its expression, resulting in an increase in endothelial cell migration [23]. Recently, Whelan et al indicated that HOXA9 overexpression induced the expression of another RTK member, the IGF-1 receptor, and subsequently promoted leukemic cell growth [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruhl et al . reported that HOXA9 bound to the EphB4 promoter and stimulated its expression, resulting in an increase in endothelial cell migration [23]. Recently, Whelan et al indicated that HOXA9 overexpression induced the expression of another RTK member, the IGF-1 receptor, and subsequently promoted leukemic cell growth [22].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of EGF to EGFR leads to receptor dimerization, autophosphorylation and the activation of several downstream signaling pathways, such as the MAPK pathway and the PI3K/Akt pathway, which play roles in cell proliferation, motility, and survival [19]; these pathways have also been shown to contribute to the abnormal growth of several types of human cancers [20]. Recent reports have demonstrated that HOX genes play a role in the regulation of several RTK family members, including EGFR [21], IGF1-receptor [22], and Eph-receptor [23,24], during development. Moreover, EGFR activation has been reported to stimulate HOXA7 expression [25].…”
Section: Introductionmentioning
confidence: 99%
“…Homeobox (HOX)-containing transcription factors emerged as one of the key regulators of Eph receptor expression. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These transcription factors contain a well conserved DNA binding motif, the homeodomain, which binds to the promoter of target genes to regulate their expression. Their spatially restricted expression patterns 34 may have a central role in establishing the graded and segmental gene expression patterns of Eph receptors during embryogenesis.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…1995, Maconochie et al, 1997Gould et al, 1997;Bergson and McGinnis,1990 ;Miller et al, 2001, Wellik andCapecchi, 2003) and that they drive conventional intercellular signalling pathways(eg. Graba et al 1995, Bruhl 2004, Manak et al1994, Michaut et al, 2011, Morsi el Kadi et al, 2002, Pearson et al, 2005 as well as acting as signalling molecules themselves (BlochGallego et al, 1993, Chatelin et al, 1996. 2.…”
Section: B Time-space Translation Timed Interactions Between the Hoxmentioning
confidence: 99%